Islamic Accounting Standard: An Intertemporal Sentiment Analysis - Syahdatul Maulida; Aam Slamet Rusydiana; Muhamad Taqi (SMART Insight, 2022)
This study aims to look at related sentiments â€œIslamic Accounting Standardâ€ around the world published by journals with that theme. This study uses a qualitative method with a sentiment analysis approach. The data used is secondary data with the theme â€œIslamic Accounting Standardâ€ obtained from the Dimensions database of 100 scientific publications. Data is processed using software SentiStrength for extracting and classifying sentiments. The results of the study found that neutral sentiment was the highest with a percentage of 39%, followed by negative sentiment with 32% and positive sentiment with a percentage of 29%. Related research Islamic Accounting Standard experienced fluctuations in the number of sentiments throughout the period 1990 to 2023. The highest number of sentiments occurred in 2018 with a total of 13 scientific publications, which were dominated by neutral sentiment of 9 scientific publications. There are several positive and negative issues related to the topic of sharia accounting standards which can be further elaborated.